Implementing Credit Agreement Restructuring During the COVID-19 Pandemic: A Case Study of PT. Bank Rakyat Indonesia (Persero) Tbk. Gombong Branch Office - Adyatma, Rafid; Anggriani , Reni (Universitas Muhammadiyah Yogyakarta, 2023)
The spread of the COVID-19 Pandemic caused a decrease in income for debtors in bank credit agreements. This resulted in debtors experiencing difficulties in fulfilling their obligations. The government, through the Financial Services Authority (OJK), issued Financial Services Authority Regulation Number 11/POJK.03/2020 as a way to restructure credit agreements for debtors who are having difficulty paying as long as the spread of the COVID-19 pandemic causes this. PT. Bank Rakyat Indonesia, as one of the banks participating in implementing this policy, restructures credit agreements for its customers who have trouble fulfilling their credit obligations by applying an analysis based on the principle of prudence.